Interpretations of the Concept of "Subject": From Classical Traditions to Post-Modern Theories - Otreshko, N. (Социология: теория, методы, маркетинг, 2015)
Scientific picture of social world includes the two fundamental concepts: the concept of social reality and that related to the subject of action/cognition/power. These concepts undergo changes depending on the historical period in which certain ideas about the major features of social reality prevail among the subjects of cognition. Classical Western philosophy and sociology have introduced the concept of subjectivity in the theories of individualism and autonomy. Those theories, in turn, have interpreted an individual as a certain unchangeable construct. However, the common idea of two recent theories developed by Norbert Elias and Judith Butler is that we need a new sociology, the sociology not dealing with unchangeable constructs but studying processes and relationships between subject and power or discourse.